2023
DOI: 10.29109/gujsc.1232071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Consumer Behavior towards Electric Vehicles: Intentions, Concerns, and Policies

Abstract: Despite the acceptance of electric vehicles (EVs) by consumers in developed countries, consumers' intentions towards these smart devices (SD) and the steps that can be taken to expand in this market continue to be investigated in developing countries such as Turkey. In this study, policies and incentives for the purchase of Electric Vehicles in different countries were examined, consumer concerns before the adoption of SDs were evaluated, and then consumer intentions in adopting EVs with models such as reasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Furthermore, the study reveals the pivotal role of knowledge about EVs in shaping individuals' perceptions and attitudes toward these vehicles. Prior research has consistently demonstrated that a well-informed population tends to view EVs as valuable, user-friendly, and acceptable, ultimately fostering their integration into the broader transportation ecosystem [14,23,26,34,84]. Therefore, efforts geared toward enhancing public knowledge about EVs can be a strategic avenue to supporting their acceptance and adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the study reveals the pivotal role of knowledge about EVs in shaping individuals' perceptions and attitudes toward these vehicles. Prior research has consistently demonstrated that a well-informed population tends to view EVs as valuable, user-friendly, and acceptable, ultimately fostering their integration into the broader transportation ecosystem [14,23,26,34,84]. Therefore, efforts geared toward enhancing public knowledge about EVs can be a strategic avenue to supporting their acceptance and adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge is an important variable in behavioural research and plays an important role in users' decisions [23,42]. Some studies [14,23,26,28,34] have revealed that users' knowledge has a substantial effect on their intentions in using innovative technologies.…”
Section: Knowledge Of Electric Vehicles (Ke)mentioning
confidence: 99%
See 1 more Smart Citation
“…It involves applying these methods to gain insights and understand scientific publication patterns [5,6]. Bibliometric analysis is a robust and systematic research method that allows for thematic analyses based on selected studies using bibliometric parameters, such as authors, citations, keywords, and publication countries [7,8]. The study obtains valuable insights and comprehensive analyses of the chosen research themes by utilizing these bibliometric parameters.…”
Section: Methodsmentioning
confidence: 99%